Crack propagation under constant amplitude loading based on an energetic parameters and fractographic analysis - Mohamed Benguediab; Benattou Bouchouicha; Zemri Mokhtar; Mohamed Mazari (Materials Research, 2012)
The crack propagation behavior in a 2024 T351 Aluminum Alloy under constant amplitude loading has been studied. This study is complemented by quantitative microfractographic observations and energetic analysis. The obtained results under constant amplitude fatigue tests show that different crack propagation stages can be identified and correlated with the evolution of the characteristic features. In another hand, the energetic analysis shows that there is a discontinuous crack growth at low growth rates as against a cycle by cycle growth mechanism at high growth rates.